2019
DOI: 10.1080/2162402x.2019.1683345
|View full text |Cite
|
Sign up to set email alerts
|

GD2-targeted chimeric antigen receptor T cells prevent metastasis formation by elimination of breast cancer stem-like cells

Abstract: 2020) GD2-targeted chimeric antigen receptor T cells prevent metastasis formation by elimination of breast cancer stem-like cells, OncoImmunology, 9:1, 1683345, ABSTRACT Expression of the disialoganglioside GD2 has been identified as a marker antigen associated with a breast cancer stem-like cell (BCSC) phenotype. Here, we report on the evaluation of GD2 as a BCSCspecific target antigen for immunotherapy. GD2 expression was confirmed at variable degree in a set of breast cancer cell lines, predominantly in tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 54 publications
0
54
0
Order By: Relevance
“…The cell surface and tumor-selective expression of GD2 has made this molecule an appealing anticancer target and has led to the development of antibody-based immunotherapies, as evidenced by the FDA-approval of the anti-GD2 monoclonal antibody dinutuximab beta for the treatment of neuroblastoma(87,88). In fact, the efficacy and long-term persistence of Epstein-Barr-viruson October 31, 2020.…”
mentioning
confidence: 99%
“…The cell surface and tumor-selective expression of GD2 has made this molecule an appealing anticancer target and has led to the development of antibody-based immunotherapies, as evidenced by the FDA-approval of the anti-GD2 monoclonal antibody dinutuximab beta for the treatment of neuroblastoma(87,88). In fact, the efficacy and long-term persistence of Epstein-Barr-viruson October 31, 2020.…”
mentioning
confidence: 99%
“…One study reported on the evaluation of disialoganglioside GD2 expressed in 35.5% of metastatic TNBC as a breast cancer stem cell specific target antigen for immunotherapy 38 . Importantly, GD2-CAR-T demonstrated excellent cytolytic activity against GD2 positive cell lines, independent of the tumor entity.…”
Section: Discussionmentioning
confidence: 99%
“…CAR-T cell therapy killed all 11 GD2-expressing cell lines studied. Seitz et al reported that GD2-directed immunotherapy by GD2-CAR-T can prevent metastasis in a highly aggressive mouse model of triple negative breast cancer (111).…”
Section: Anti-gd2 Car-t Cellsmentioning
confidence: 99%